Efektivitas Komunikasi melalui ‘Whatsapp’ pada Pembelajaran Jarak Jauh (PJJ) - Nur Faisal Nazar; Yenni Yuniati (UNISBA Press, 2022)
Abstract. When the Covid-19 pandemic hits, every activity that is carried out every day must be delayed or even not carried out. Like gathering with friends, chatting in the office at one table, even studying at school can't be done. The learning process carried out has not been carried out optimally, so that learning is carried out online (online) which is commonly referred to as Distance Learning (PJJ). Distance Learning has problems in terms of communication, especially in mathematics which according to students is very difficult to understand. Therefore, in his arms there is a communication platform that can be used by everyone, for example social media. The objectives are to determine the use of communication tools in the form of WhatsApp social media, to determine whether the learning process in mathematics subjects can be carried out effectively with the Distance Learning process, and to determine the effect of using Whatsapp social media to affect the learning process in the eyes. mathematics. The research method used is quantitative correlation. The research instrument used interviews and questionnaires, where observations were made beforehand to determine the relationship between communication through social media